2019
DOI: 10.3390/en12030507
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Cost-Effectiveness of the Installation of Heat-Cost Allocators in Multifamily Buildings in Croatia

Abstract: In order to improve energy efficiency, the Croatian government introduced an individual metering obligation for all district heat network users. The purpose of the research was to evaluate this policy measure regarding its effects on tenants’ behavior and energy savings, but also from the perspective of cost-effectiveness. The sample includes approximately 20% of all Croatian users of district heat energy. Energy savings related to the installation of heat cost allocators are calculated by comparing the specif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Two studies experimentally evaluated the potential for energy saving of heat accounting and temperature control devices in temperate climates: the first [20], conducted in about 3000 apartments in three Italian cities, highlighted a wide variability of energy consumption variation (ranging from -24% to +15%, on average 11%) showing a higher potential for energy saving in temperate climates rather than in cold ones; the second [19], conducted in Spain, found a 15-20% reduction of normalized energy consumption during the first two years after HCAs and TRVs installation. In [21] a saving ranging between 21-36% and in average of 25% has been found in Croatia, thus ensuring a positive net present value if the specific energy requirements of the apartment are lower than 170 kWh/m 2 and 95 kWh/m 2 in Continental and Mediterranean Croatia, respectively. This is due to the difference in heat energy price between cities in Continental and Mediterranean Croatia.…”
Section: Benefit Estimation From Individual Heat Metering and Accountingmentioning
confidence: 97%
See 1 more Smart Citation
“…Two studies experimentally evaluated the potential for energy saving of heat accounting and temperature control devices in temperate climates: the first [20], conducted in about 3000 apartments in three Italian cities, highlighted a wide variability of energy consumption variation (ranging from -24% to +15%, on average 11%) showing a higher potential for energy saving in temperate climates rather than in cold ones; the second [19], conducted in Spain, found a 15-20% reduction of normalized energy consumption during the first two years after HCAs and TRVs installation. In [21] a saving ranging between 21-36% and in average of 25% has been found in Croatia, thus ensuring a positive net present value if the specific energy requirements of the apartment are lower than 170 kWh/m 2 and 95 kWh/m 2 in Continental and Mediterranean Croatia, respectively. This is due to the difference in heat energy price between cities in Continental and Mediterranean Croatia.…”
Section: Benefit Estimation From Individual Heat Metering and Accountingmentioning
confidence: 97%
“…Several studies conducted in central EU countries demonstrated potential benefits variable between 8% and 40% [16][17][18] whereas more recent studies in Mediterranean countries found lower benefits: i) variable between 10-20% [19], ii) in average of about 11% but highlighting also increased consumptions in some investigated buildings (up to 24%) [20], iii) variable between 21-36% and in average 25% (with 16% of investigated apartments showing increased consumptions) [21]. Besides, standard figures of cost related to the installation of individual metering systems are available only for few markets [5,6,22,23].…”
Section: Introductionmentioning
confidence: 99%